I saw Poland suffer (London: Lindsay Drummond, 1941)
"by a Polish doctor who held an official position in Warsaw under German occupation ; translated and arranged by Alcuin ; With additional chapters on Poland to-day by Alcuin Bibliotheek Camille Huysmans"